An analysis of law enforcement cooperation in child sex tourism cases involving Thailand and Canada. (25th January 2021) - de Vries, Samantha
ABSTRACT: Thailand and Canada share an interest in improving international cooperation in the investigation and prosecution of child sex tourism cases. Both countries have made international commitments to protect children from violence and sexual exploitation. Despite these commitments, child sexual exploitation by some Canadians still occurs in Thailand for complex reasons, including a lower risk of detection, the availability of poor and vulnerable children, lack of political will, and an established sex tourism industry. To understand how law enforcement cooperation can be improved in these cases interviews with twenty-four participants (criminal justice officials and NGO representatives) working in Thailand and Canada document their respective experiences of international cooperation, various challenges, and possible recommendations for improvement. Key findings include the importance of interagency cooperation and collaboration among foreign police based in Thailand, and barriers to effective cooperation such as admissibility of foreign evidence, involvement of non-police organizations in police operations, and lengthy diplomatic processes.